2000
DOI: 10.1016/s0550-3213(00)00482-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical symmetry breaking in supersymmetric and gauge theories

Abstract: We find the phase and flavor symmetry breaking pattern of each N = 1 supersymmetric vacuum of SU (n c ) and U Sp(2n c ) gauge theories, constructed from the exactly solvable N = 2 theories by perturbing them with small adjoint and generic bare hypermultiplet (quark) masses. In SU (n c ) theories with n f ≤ n c the vacua are labelled by an integer r, in which the flavor U (n f ) symmetry is dynamically broken to U (r) × U (n f − r) in the limit of vanishing bare hyperquark masses. In the r = 1 vacua the dynamic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
236
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(258 citation statements)
references
References 43 publications
22
236
0
Order By: Relevance
“…In contrast to the theories considered in [8], SO(n c ) gauge theories with quarks in the vector representation present a clear distinction between Higgs and confinement phases since the behavior of the Wilson loop in the spinor representation is qualitatively different in the two cases. Therefore, unlike other examples (as in [2] for SU (2)) a Higgsed-vacuum in the semiclassical regime (large m i ) must remain in the Higgs phase in the strong-coupling regime (m i → 0) as well.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…In contrast to the theories considered in [8], SO(n c ) gauge theories with quarks in the vector representation present a clear distinction between Higgs and confinement phases since the behavior of the Wilson loop in the spinor representation is qualitatively different in the two cases. Therefore, unlike other examples (as in [2] for SU (2)) a Higgsed-vacuum in the semiclassical regime (large m i ) must remain in the Higgs phase in the strong-coupling regime (m i → 0) as well.…”
Section: Introductionmentioning
confidence: 80%
“…In their subsequent work [2] they also showed that in theories with matter hypermultiplets, flavor symmetries are broken dynamically by the condensation of monopole multiplets transforming under certain representations of the flavor group. Although their analysis of the low-energy effective action and confinement mechanism was extended to more general theories ([3] [4] [5] [6] [7]), the dynamics of flavor symmetry breaking for more general gauge theories has only recently been investigated in [8] for SU (n c ) and USp(2n c ) gauge groups. Similar techniques, when applied to SO(n c ) gauge theories, yield results with some unexpected features.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this subsection we will try to understand this vacuum structure of the gauge theory at both classical and quantum levels for a specific model (for more details, see [10,11,12,13,14,15]). For simplicity we will focus on U(N c ) theory with N f flavors and the following tree level superpotential 3…”
Section: The Vacuum Structurementioning
confidence: 99%